Microcontroller Implementation for Automatic Smart Bell - Annas, Muhammad Sabri; Haripuddin, Haripuddin; Zain, Satria Gunawan (International Journal of Environment, Engineering & Education, 2019)
This study aims to design automatic school bell hardware based on the ATmega32 microcontroller, design automatic school bell software based on the ATmega32 microcontroller using Basic programming language, and test the performance of the automatic school bell based on the ATmega32 microcontroller. This automatic school bell uses a minimum system of ATmega32 microcontrollers which equipped with data input from the push button, LCD to display character output, ISD2560 to output sound, and a timer taken from DS1307 RTC. This research is a Research or Development (R & D) research. This research is carried out through two stages of design. The first stage is the stage of hardware design. The second stage is the stage of software design. Programs are made using the Basic programming language using the Bascom-AVR application. The results of the product were tested using the black box method with two stages. In the first stage, software testing uses a series of simulations on the Proteus 7 Professional application. The second stage, testing hardware.